Culture et droit processuel : le cas du Québec - Jutras, Daniel (McGill Law Journal, 2009)
This article considers the influence of culture within Quebec’s procedural law, building upon the recent reform of the Code of Civil Procedure. The author affirms that the distinctiveness of Quebec’s procedural law resides in its mixed culture, which is the product of the superimposition of different perspectives on the institutional values and symbols of the state’s dispute-processing mechanisms.